THE IMPORTANCE OF ARTICULATION EXERCISES IN SPEECH THERAPY (American Journal of Interdisciplinary Research and Development, 2023)
This article discusses the importance of articulation exercises for children who have speech impediments and highlights the factors that contribute to it.